Etanolic extract of Ling Zhi Mushroom (Ganoderma lucidum) improves lipid profile, CRP and histopathological of liver in dislipidemia model rats - Soegianto, Jap Yulius Billy; Samodro, Pugud; Wisesa, Sindhu; Hernayanti, Hernayanti; Setyono, Joko; Arjadi, Fitranto (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2023)
.